Effects of quinolones on nucleoid segregation in Escherichia coli. - Georgopapadakou, N H (1991)
The effects of quinolone antibiotics on nucleoid segregation in growing Escherichia coli were examined by using fleroxacin (Ro 23-6240, AM 833) as a prototype compound. At levels that were close to its MIC and induced growth arrest and filamentation, fleroxacin caused large nucleoids to appear in midcell, suggesting inhibition of nucleoid segregation. With increasing fleroxacin concentrations, nucleoids became progressively smaller, suggesting inhibition of DNA replication. Removal of fleroxacin restored normal cell and nucleoid morphology in filaments with large nucleoids but not in filaments with small nucleoids. The results are consistent with inhibition of chromosome decatenation at low quinolone concentrations (bacteriostatic effect) and DNA supercoiling at high concentrations (bactericidal effect).